Factors Influencing Chinese Dialect Variation: An SLR Based on a Multidisciplinary Approach - Dimas Fajar Praditya; Handika Cahaya Danuarta; Dwiki Wahyudi; Muhammad Reza Rahmansyah; Mintowati; Rokhishotul Amaliyah (Yayasan Kyadiren, 2026)
This study examines the factors influencing Chinese dialect variation from a sociolinguistic perspective. Despite the establishment of Putonghua as the national standard language, various dialects such as Yue, Min, Wu, and Hakka continue to be used in daily communication, reflecting linguistic and cultural diversity within Chinese society. This research aims to identify and synthesize the main factors affecting dialect variation through a Systematic Literature Review (SLR) approach. Relevant articles published between 2020 and 2025 were collected and analyzed from reputable academic sources. The findings reveal that Chinese dialect variation is shaped by four major factors: social factors, including urbanization, mobility, and language contact; geographical factors, such as regional isolation and topographical conditions; historical-political factors, including migration patterns and language policies; and language identity factors related to cultural attachment and community belonging. The study also indicates that the dominance of Mandarin has contributed to language shift among younger generations.